Odpowiedź :
Rozwiąż równania
a)
³-x/₆ - ²+x/₃ =1 /*6
3-x -2(2+x)=6
3-x-4-2x=6
-3x=6-3+4
-3x=7
x=-7/3
b)
5+|x+1|=8
|x+1|=8-5
|x+1|=3
x+1=3 lub x+1=-3
x=2 lub x= -4
a)
³-x/₆ - ²+x/₃ =1 /*6
3-x -2(2+x)=6
3-x-4-2x=6
-3x=6-3+4
-3x=7
x=-7/3
b)
5+|x+1|=8
|x+1|=8-5
|x+1|=3
x+1=3 lub x+1=-3
x=2 lub x= -4
Rozwiąż równania
a)
(³-x)/₆ - (²+x)/₃ =1 /*6
3-x -(2+x)=6
3-x-2-x=6
-2x=6-3+2
-2x=5
x=-5/3
b)
5+|x+1|=8
|x+1|=8-5
|x+1|=3
x+1=3 v x+1=-3
x=2 v x= -4
a)
(³-x)/₆ - (²+x)/₃ =1 /*6
3-x -(2+x)=6
3-x-2-x=6
-2x=6-3+2
-2x=5
x=-5/3
b)
5+|x+1|=8
|x+1|=8-5
|x+1|=3
x+1=3 v x+1=-3
x=2 v x= -4